Socialization of the Use of Google Gemini to Improve the Quality of Teaching and Learning, the Quality of Financial Management, and the Quality of Marketing of MSMEs in Indonesia - Muhamad Irfan Florid; Melvianus Selan; Fransiskus Dwikotjo Sri Sumantyo; Heppi Syofya; Tarjono (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service program aims to accelerate the adoption of Generative Artificial Intelligence technology through the socialization of the use of Google Gemini in four strategic regions of Indonesia. Implementation was carried out specifically at the University of North Sumatra (Medan) to represent the Sumatra cluster, the National Industrial Design Center (Yogyakarta) for the Java cluster, the Integrated Business Service Center/PLUT-KUMKM (Pontianak) for the Kalimantan cluster, and Makassar Digital Valley (Makassar) for the Sulawesi cluster. This program targets three main pillars: increasing the efficiency of teaching tools for educators, digitizing independent financial reports, and optimizing marketing copywriting for MSMEs. The methods used were participatory workshops and technical assistance. Evaluation results showed that the use of Google Gemini was able to reduce administrative time for educators by up to 60% and significantly improve the quality of MSME digital promotional content. This program proves that equalizing AI literacy across Indonesia's major islands is key to strengthening economic competitiveness and the quality of national education